1992
DOI: 10.1203/00006450-199206000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Rhythmic Swallowing and Breathing during Suckle Feeding in Term Neonates

Abstract: ABSTRACT. Little is known of the development of efficient coordination between suckle feeding and breathing in human infants. To establish baseline data, we recorded breathing and swallowing activity during bottle feeds in 23 infants at 14-48 h postnatal age. Most swallows (overall mean 68%) were organized into runs, with intervals starting at 0.6-0.8 s and slowing to 1-1.3 s after 30-40 s. The proportion of run swallows to total swallows increased significantly with age. Swallow intervals were regular (coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 17 publications
4
82
2
1
Order By: Relevance
“…On the other hand, age expressed in terms of PMA correlates better with the development of sucking and swallowing than chronological age, which presumes that oral feeding is a congenital behavioral pattern rather than acquired behavior. 28 Lau and Kusnierczyk 6 divided the normal maturational process into five primary stages based on the presence or absence of suction and rhythmicity for the two components of sucking: suction and expression/compression (Table 1). Lau and Kusnierczyk 6 used this scale to indicate the relation between the development of sucking and the preterm infant's oral feeding skill.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, age expressed in terms of PMA correlates better with the development of sucking and swallowing than chronological age, which presumes that oral feeding is a congenital behavioral pattern rather than acquired behavior. 28 Lau and Kusnierczyk 6 divided the normal maturational process into five primary stages based on the presence or absence of suction and rhythmicity for the two components of sucking: suction and expression/compression (Table 1). Lau and Kusnierczyk 6 used this scale to indicate the relation between the development of sucking and the preterm infant's oral feeding skill.…”
Section: Introductionmentioning
confidence: 99%
“…This impression was confirmed by analysis of the feeding records. A run was defined as three or more swallows occurring at intervals of less than 2 s [10]. A swallowswallow interval of 2 s or more was considered to mark the end of a run.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Selley et al [2] reported that the predominant pattern was inspiration-swallow-expiration in 15 of 19 infants, and an average of 83% of swallows were followed by expiration. Bamford et al [10] examined the coordination between swallowing and breathing in the normal newborn infant at age less than 48 h. They found considerable variability in the phase relationship between swallows and breaths in early neonatal life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations